The Impact of Consumer Attitudes and Brand Perception on Purchase Intentions: A Study of Health and Wellness Products in Haryana (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Our research investigates the relationship between consumer attitudes, brand perception, and purchase intentions in Haryana's health and wellness product market. Through comprehensive primary research involving 250 respondents across major cities in Haryana, we examined how attitudes and brand perceptions influence consumer purchase decisions. Using a quantitative approach, the research employed structured questionnaires and statistical analysis to examine these relationships. The findings reveal significant correlations between consumer trust, brand perception, and purchase intentions (r=0.76, p<0.001). Urban consumers demonstrated significantly higher health consciousness scores (M=4.4, SD=0.62) compared to rural consumers (M=3.9, SD=0.71). The study contributes to understanding regional consumer behavior in India's evolving health and wellness market, providing valuable insights for marketers and brand managers.